PERANCANGAN MESIN PENCACAH PAKAN TERNAK MULTIFUNGSI MENGGUNAKAN SYSTEM PENGGERAK MOTOR BAKAR BENSIN - nalahuddin, Muchlisi; Saputra, Candra; Arief, Rudi Kurniawan (Jurnal Ilmiah Poli Rekayasa, 2024)
This research introduces the design of a multifunctional animal feed chopper machine using a gasoline engine as the driving system. The gasoline engine used is Ecolite TE160 5.5 HP which can provide reliable power and performance to drive the feed chopper machine. The test material used is banana stems which are effectively finely chopper to obtain consistent and high quality chopper results. This design methodology includes identification of needs, mechanical design, material selection and testing of the tool. The working method of this machine is to insert the banana stem into the input hopper where the chopper knife rotates using a gasoline engine as the driving source. The chopper blade is specially designed with sharpness and thickness that suits the needs needed to get maximum and effective chopper results. The frame of this multifunctional animal feed chopper machine uses L 35 mm x 35 mm x 2.5 mm profile steel with a size of 105 cm long x 35.5 cm wide x 72.5 cm high. From the data obtained, the engine rotation used is 2500 Rpm. The results of testing this machine can be concluded that the heavier the material to be chopper, the longer the chopper time obtained, the thickness obtained is consistently 1.3 cm thick. Overall the development of a multifunctional animal feed chopper machine represents a significant advancement in pemp technology